Benzothiazole sulfonate derivatives bearing azomethine: Synthesis, characterization, enzyme inhibition, and molecular docking study - Korkmaz, Adem; Bursal, Ercan (Elsevier, 2022)
Enzyme inhibition is one of the most applied ways to find new diagnostic facilities for the prevention and treatment of many health problems. Tyrosinase and pancreatic lipase inhibitions have been used for the treatment of skin pigmentation problems and obesity, respectively. This study mainly focused to evaluate the enzyme inhibitions of the newly synthesized sulfonate derivatives ( 3a -3i ) for tyrosinase and pancre-atic lipase. The structural characterizations of the 2-(((5-methylbenzo[d]thiazol-2-yl)imino)methyl)phenyl sulfonate derivatives were performed by H-1 NMR, C-13 NMR, and HR-MS analyses. According to the in vitro enzyme inhibition methods, compound 3e had the highest tyrosinase inhibitory activity (46.9 & nbsp;+/- 3.6 mu M IC50 value). On the other hand, the effective pancreatic lipase inhibitory activities of the compounds 3f, 3e , and 3g were determined from their low IC50 values 58.3 & nbsp;+/- 6.7 mu M, 59.5 & nbsp;+/- 13.8 mu M, and 64.8 +/-& nbsp;6.3 mu M, respectively. Molecular docking studies were also conducted for the synthesized com-pounds with tyrosinase and pancreatic lipase enzymes separately. Finally, the ADME studies were carried out to determine the pharmacokinetics, drug similarities, and medicinal properties of the target com-pounds.. (C)& nbsp;2022 Elsevier B.V. All rights reserved.
Keywords: Enzyme inhibition; Benzothiazole; Azomethine; Molecular docking; ADME; Sulfonate; In-Vivo